Legal Protection for Participants in the Benefit Sharing Scheme between BPJS Kesehatan and Commercial Insurance - Putu Nur Idayanthi; Nyoman Ariana; Anak Agung Gede Duwira Hadi Santosa (Journal of Law, Politic and Humanities, 2025)
This study examines the legal protection mechanisms for participants in the benefit-sharing scheme between BPJS Kesehatan and commercial insurance providers. The background of this research is driven by the increasing collaboration between national health insurance administrators and private insurance companies, which raises legal challenges, particularly concerning the clarity of participants' rights and obligations. The research adopts a normative approach, involving regulatory document analysis and case studies. The findings indicate the existence of legal gaps that cause uncertainty in participant protection, with regulatory ambiguities and differing interpretations between national legal norms and commercial insurance practices emerging as key issues. These findings highlight the need for regulatory harmonization and policy adjustments to ensure the benefit-sharing mechanism operates transparently and accountably. The research recommendations include improving the regulatory framework, drafting clear operational guidelines, and enhancing supervisory roles to ensure fairness and legal certainty for all participants. Thus, this study is expected to contribute to the development of more adaptive and responsive health law policies in line with the evolving dynamics of Indonesia’s health insurance system.